From Variability to Visibility: Mitigating the Bullwhip Effect in Modern Supply Chains - Salwa, Nisrina; Zulfikri , Agung (Yayasan Sinergi Kawula Muda, 2024)
The bullwhip effect (BWE) remains a significant challenge in supply chain management, marked by demand amplification that disrupts inventory systems and reduces efficiency. This narrative review explores the causes, systemic factors, and mitigation strategies of BWE, based on literature from 2015 to 2024 sourced from Scopus and Google Scholar. Key contributors to BWE include lead time variability, inventory inaccuracies, and behavioral decision-making, alongside the roles of distribution structures and ordering policies. Technological solutions such as neural networks, blockchain, RFID, and ERP systems help reduce BWE by improving forecasting and visibility. Additionally, practices like cross-docking, vendor-managed inventory, and real-time data sharing support inventory stability and coordination. The review emphasizes the need for integrated tech-driven and behavioral approaches, advocating for interdisciplinary, longitudinal, and sector-specific future research to build more resilient supply chains. These insights are vital for organizations aiming to improve performance, cut costs, and adapt to global market complexities.